Trivalent Phospha-Brook rearrangement enabled practical deoxygenative phosphonylation of carbonyls - Xiaoqiang Wu; Shanya Lu; Wei Zhong; Tao XU (Nature Communications)
Abstract Brønsted base-mediated [1,2]-phospha-Brook rearrangements have garnered considerable attention for developing new methodologies and efficiently constructing complex molecular structures. However, the strict reliance on pentavalent phosphonates imposes strong limitations on the reaction types, and the mechanistic constraint also excludes the involvement of trivalent phosphine in the same pathway. In this study, we employ Lewis acid rather than Brønsted base to shift the charge transfer from the previous O-P-C direction to a P-C-O process. This orthogonal approach can undergo the unprecedented C–O bond cleavage instead of traditional C–P bond splitting and enables the deoxygenative phosphorylation of carbonyl compounds under metal-free conditions to rapid access various tertiary phosphine oxides. The reaction demonstrates excellent substrate scope, remarkable functional group compatibility, and operational simplicity, offering significantly enhanced atom-economy compared to previous deoxygenative strategies. Additionally, detailed mechanistic studies reveal an unusual oxygen atom crossover and clearly elucidate the mechanism of this Lewis acid-mediated trivalent phospha-Brook rearrangement. These insights further deepen the understanding of trivalent phosphorus chemistry and pave the way for the design of related reactions.